The Alleviation of Dextran Sulfate Sodium (DSS)-Induced Colitis Correlate with the logP Values of Food-Derived Electrophilic Compounds - Xiang-Rong Cheng; Bu-Tao Yu; Jie Song; Jia-Hui Ma; Yu-Yao Chen; Chen-Xi Zhang; Piao-Han Tu; Mitchell N. Muskat; Ze-Gang Zhu (MDPI AG, 2022)
Food-derived electrophilic compounds (FECs) are small molecules with electrophilic groups with potential cytoprotective effects. This study investigated the differential effects of six prevalent FECs on colitis in dextran sodium sulfate (DSS)-induced mice and the underlying relationship with molecular characteristics. Fumaric acid (FMA), isoliquiritigenin (ISO), cinnamaldehyde (CA), ferulic acid (FA), sulforaphane (SFN), and chlorogenic acid (CGA) exhibited varying improvements in colitis on clinical signs, colonic histopathology, inflammatory and oxidative indicators, and Nrf2 pathway in a sequence of SFN, ISO > FA, CA > FMA, CGA. Representative molecular characteristics of the "penetration-affinity-covalent binding" procedure, logP value, Keap1 affinity energy, and electrophilic index of FECs were theoretically calculated, among which logP value revealed a strong correlation with colitis improvements, which was related to the expression of Nrf2 and its downstream proteins. Above all, SFN and ISO possessed high logP values and effectively improving DSS-induced colitis by activating the Keap1-Nrf2 pathway to alleviate oxidative stress and inflammatory responses.